2012
DOI: 10.1007/s10593-012-0977-3
|View full text |Cite
|
Sign up to set email alerts
|

Novel data for the reaction of 3-cyano-(thio)chromones with N-nucleophiles

Abstract: Recent literature data for the reaction of 3-cyano(thio)chromones with amines, hydrazines, and hydroxylamine are summarized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…1,2,4‐Triazepane 84 was prepared from the reaction of chromone 82 with 1,6‐diamino‐4‐(4‐chlorophenyl)‐2‐oxo‐1,2‐dihydropyridine‐3,5‐dicarbonitrile 83 in DMF under reflux conditions (Scheme ) …”
Section: Discussionmentioning
confidence: 99%
“…1,2,4‐Triazepane 84 was prepared from the reaction of chromone 82 with 1,6‐diamino‐4‐(4‐chlorophenyl)‐2‐oxo‐1,2‐dihydropyridine‐3,5‐dicarbonitrile 83 in DMF under reflux conditions (Scheme ) …”
Section: Discussionmentioning
confidence: 99%
“…A lithium dialkynylcuprate as [(TMS-C≡C) 2 CuLi], though capable of transferring its alkynyl group in a conjugate addition to the ester 6e, failed to react with 3-alkoxycarbonyl-2-methylchromone 5. Heteroannulation of the chromone A (≡ 2, 3, 5a) with 2-chloroethanol in the presence of K 2 CO 3 to the corresponding furobenzopyranone 101 (Equation 8) proceeds via the conjugate addition of the haloethanol to the chromone followed by intramolecular alkylation.…”
Section: Scheme 14mentioning
confidence: 99%
“…Later Li et al 86 reported that the product 157, if prepared from 118a and 155, remains admixed with the benzothiazole 158; it can be had exclusively by treating the acid chloride 159 with the thiophenol 155 in N-methyl-2-pyrrolidone at 100 °C. A mixture of Zn(OAc) 2 and potassium salt of thiazole 157 in a molar ratio of 1:2 in MeOH-H 2 O forms the four coordinated Zn(II) complex 160. as well as with phenyltrimethylammonium tribromide 91 give the corresponding 3-bromoacetylchromones (Equation 10), the latter reagent being claimed to improve the yield.…”
Section: Scheme 20mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, chromone derivatives were used in diverse optoelectronic applications . Introduction of an electron‐withdrawing group into the 3‐position of chromone changes the reactivity of the γ‐pyrone ring towards nucleophilic reagents and opens up a broad synthetic scope of this important oxygen‐containing heterocyclic systems . 3‐Substituted chromones are very active substrates for nucleophilic attack at C‐2 position and used as valuable synthetic intermediates in the preparation of a variety of heterocyclic compounds .…”
Section: Introductionmentioning
confidence: 99%